Exploring factors influencing purchase intention on semi-prepared food among Malaysia consumers/ Hairunnisa Mohamad Ibrahim, Azuralisda Mohd Ghazali and Zuratulraha Jaafar - Mohamad Ibrahim, Hairunnisa; Mohd Ghazali, Azuralisda; Jaafar, Zuratulraha (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2021)
The purpose of this study is to discover Malaysian millennial consumer attitudes in the direction of semi-prepared food and their purchase objective. The objective set for this research was conducted with the following objectives respectively getting an insight into the semi- prepared food market in Malaysia and explore the attributes that local consumers attitude consumption and determine the relationship between each dimension(s) of consumers' attitude towards purchase intention of semi- prepared food. The study results supply a preferable understanding of the market as well as consumer mindset intake variables. The design and the style of the set of the questionnaire in this research study were based on the actions of previous associated studies as well as literary works evaluation that has been established and utilized in the present research. Results have shown to be a legitimate mechanism for the dimension with 5 factors (Health Risk, Nutritional Value, Family Orientation, Value for Money, and Convenient & Lifestyle) toward with Purchase Intention. In this regard, other questions such as demographic information have been added in this research. Moreover, the findings showed that there is a significant positive relationship between the purchase intentions and three variables which are Health Risk, Nutritional Value, and Family Orientation. As intention to purchase is an important indicator of consumer attitude consumption, the industry may use results as part of the tool when promoting and enhance acceptance of semi- prepared among the consumers.